2016
DOI: 10.1093/jisesa/iew019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nanopillars on the Cuticle of the Aquatic Larvae of the Drone Fly (Diptera: Syrphidae)

Abstract: Here, we describe a nano-scale surface structure on the rat-tailed maggot, the aquatic larva of the Drone fly Eristalis tenax (L.). Larvae of this syrphid hover fly live in stagnant, anaerobic water-courses that are rich in organic matter. The larvae burrow into fetid slurry and feed on microorganisms which they filter out from the organic material. This environment is rich in bacteria, fungi and algae with the capacity to form biofilms that might develop on the larval surface and harm them. Using transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Watson et al, demonstrated the bactericidal effect on P. gingivalis, caused by the micro-and nanosurface of gecko skin, which consists of spinules with a radius of curvature smaller than 20 nm and spacing in the sub-micron range [35]. Another group suggested that the hydrophilic surface texture of nanopillars on the aquatic larvae of the drone fly might inhibit biofilm formation and may even be bactericidal [36]. By using an alkaline hydrothermal process Diu et al, introduced a potent titanium nanostructured surface with two different phenotypes: brush and niche type nanowires with a diameter of approximately 100 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Watson et al, demonstrated the bactericidal effect on P. gingivalis, caused by the micro-and nanosurface of gecko skin, which consists of spinules with a radius of curvature smaller than 20 nm and spacing in the sub-micron range [35]. Another group suggested that the hydrophilic surface texture of nanopillars on the aquatic larvae of the drone fly might inhibit biofilm formation and may even be bactericidal [36]. By using an alkaline hydrothermal process Diu et al, introduced a potent titanium nanostructured surface with two different phenotypes: brush and niche type nanowires with a diameter of approximately 100 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Many insects take advantage of this wetting physics and attain superhydrophobicity by both coating their bodies with oil or wax to optimize their surface chemistry 3 , 10 , 11 , and using hierarchical roughness structures to maximize the air fraction (minimize the solid-liquid contact) between the liquid and their bodies 4 . The roughness appears in many forms in insects and plants alike, including: nanopillars on drone fly 12 and dragonfly wings 13 , micropapillae on lotus leaves 14 , micropapillae with nanofolds on rose petals 15 , needle shaped setae with nanogrooves on water strider 11 , 16 and crane fly legs 17 , and arrays of hair with star-shaped cuticular projections on termite wings 18 . Insect surface chemistry and roughness helps them to stay dry, but their interactions with water brings other challenges as well.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, more naturally occurring bactericidal surfaces have been reported . They include nanopillars on the dragonfly wing, the damselfly wing, the moth eye, the rat‐tailed maggot, the aquatic larva of the Drone fly, and the nanotipped hairs on gecko skin …”
Section: Antimicrobial Nanotopographiesmentioning
confidence: 99%